High‐Performance Near‐Infrared Photodetectors Based on Surface‐Doped InSe. (16th October 2020) - Jang, Hanbyeol; Seok, Yongwook; Choi, YiTaek; Cho, Sang‐Hoo; Watanabe, Kenji; Taniguchi, Takashi; Lee, Kayoung
Abstract: 2D InSe is one of the semimetal chalcogenides that has been recently given attention thanks to its excellent electrical properties, such as high mobility near 1000 cm 2 V −1 s −1 and moderate band gap of ≈1.26 eV suitable for IR detection. Here, high‐performance visible to near‐infrared (470–980 nm wavelength (λ)) photodetectors using surface‐doped InSe as a channel and few‐layer graphenes (FLG) as electrodes are reported, where the InSe top region is relatively p ‐doped using AuCl3 . The surface‐doped InSe photodetectors show outstanding performance, achieving a photoresponsivity ( R ) of ≈19 300 A W −1 and a detectivity ( D *) of ≈3 × 10 13 Jones at λ = 470 nm, and R of ≈7870 A W −1 and D * of ≈1.5 × 10 13 Jones at λ = 980 nm, superior to previously reported 2D material‐based IR photodetectors operating without an applied gate bias. Surface doping using AuCl3 renders a band bending at the junction between the InSe surface and the top FLG contact, which facilitates electron‐hole pair separation and immediate photodetection. Multiple doped or undoped InSe photodetectors with different device structures are investigated, providing insight into the photodetection mechanism and optimizing performance. Encapsulation with hexagonal boron nitride dielectric also allows for 3‐month stability. Abstract : High‐performance InSe photodetectors are demonstrated by surface doping via AuCl3 solution and possessing graphene as contacts on the top and bottom of the AuCl3 ‐doped InSe. The surface doping induces band bending at the junction between the InSe surface and the top graphene contact, which facilitates electron‐hole pair separation and immediate photodetection.